Global Pharmaceutical Industries, Drugs Exploration and Patenting: Impact On Developing Countries - Ari Satia Nugraha (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2007)
Globalization has contributed to the development of pharmaceutical industries in terms of medical exploration and trade among countries araund the world. A number of pharmaceutical companies have been established throughout the world and become international businesses. Nowadays, pharmaceutical businesses in developed countries are more likely to embrace global agreement on intellectual properties and trade designed to keep competition fair. Multinational Pharmaceutical Companies (most of them are from developed countries) play a large role in both drug development and supply. According to ABPI in 2004, more than 60% of the world’s drugs consumption is supplied by only 20 big pharmaceutical corporations. Can it be argued that multinational pharmaceutical companies give benefit for pharmaceutical companies and people in developing countries around the world? This article will focus on several negative impacts occurred on developing countries.